The Effect of Work Motivation and Organizational Culture on Employee Performance Department of Population Control and Family Planning, Karawang District - Herlina Yunita; Uus MD Fadli; Laras Ratu Khalida (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study intends to ascertain the impact of organizational culture and work motivation on the productivity of Karawang Regency's Population Control and Family Planning Office staff. The population and family planning office of the Karawang Regency provided 41 respondents for the saturated sample, which was created using a non-probability sampling technique. The primary data used was collected directly from the respondents and went through analysis and processing. Data processing using SmartPLS 3.0 software's Path analysis (Path analysis) tools. Using the SmartPLS 3.0 Software, the following tests were run: convergent validity test, discriminant validity test, reliability test, t-statistic test, hypothesis test, coefficient of determination test, and effect size test. The research's findings are: 1. Organizational culture and work motivation are strongly and favorably correlated. 2. Work motivation has a limited impact on employee performance. 3. Organizational culture has a limited impact on worker performance. 4. Both company culture and work motivation have an impact on employees' performance.